How Does Environmental Data from ESG Concept Affect Stock Returns: Case of the European Union and US Capital Markets - Giedrė Lapinskienė; Dainora Gedvilaitė; Aušra Liučvaitienė; Kęstutis Peleckis (Emerging Science Journal, 2023)
This article examines the environmental, social, and governance (ESG) performance of firms, with a focus on the environmental pillar of the ESG concept. It is believed that the price of equities as well as sector-specific characteristics may be affected by ESG data. It also contributes to the argument that environmental performance and governance quality are related. The purpose of this paper is to statistically validate the separated environmental data from the ESG concept and investigate its impact on the equity price in the EU and the United States. Using simple linear regressions and a fixed effect panel data model, the association between environmental score and governance score, as well as equity price and environmental score, was estimated. This study examines the 500 largest US corporations comprising the S&P 500 index (S&P) and the 600 largest EU companies comprising the STOXX Europe 600 index (STOXX) (SXXP). This article analyzes ESG statistics for the period 2015–2020. The results indicate that a higher government score has a favorable effect on environmental pledges and that changes in stock price depend in part on environmental data. The novel contribution of this paper is that the results suggest a sector-specific contribution to the model, and it would be fascinating to analyze sector disparities and their ESG-related policies in greater detail. Doi: 10.28991/ESJ-2023-07-02-08 Full Text: PDF